N-acetylcysteine decreases lung inflammation and fibrosis by modulating ROS and Nrf2 in mice model exposed to particulate matter. (2nd November 2022) - Choi, Seon-Muk; Lee, Pureun-Haneul; An, Min-Hyeok; Yun-Gi, Lee; Park, Shinhee; Baek, Ae Rin; Jang, An-Soo
Abstract: Background and Objectives: Air pollutants can induce and incite airway diseases such as asthma. N-acetylcysteine (NAC) affects signaling pathways involved in apoptosis, angiogenesis, cell growth and arrest, redox-regulated gene expression, and the inflammatory response. However, it is not known how NAC change redox-regulated gene expression in asthma mouse model exposed to particulate matter (PM). To investigate the effects of NAC on asthma mice exposed to PM through Reactive oxygen species (ROS), nuclear factor erythroid 2-related factor 2 (Nrf2), and mucin 5 (Muc5). Methods: To investigate the effects of NAC (100 mg/kg) on redox-regulated gene expression and lung fibrosis in a mouse model of asthma exposed to PM. A mice model of asthma induced by ovalbumin (OVA) or OVA plus titanium dioxide (OVA + TiO2 ) was established using wild-type BALB/c female mice, and the levels of Nrf2 and mucin 5AC (Muc5ac) proteins following NAC treatment were examined by Western blotting and immunostaining. In addition, the protein levels of ROS were checked. Results: Airway hyperresponsiveness and inflammation, goblet cell hyperplasia, and lung fibrosis were higher in OVA, OVA + TiO2 mice than in control mice. NAC diminished OVA + TiO2 -induced airway hyperresponsiveness and inflammation, goblet cell hyperplasia, and lung fibrosis. Levels of ROS, Nrf2, and Muc5ac protein were higher in lung tissue from OVA + TiO2 mice than that from control mice and were decreased by treatment with NAC. Conclusions: NAC reduce airway inflammation and responsiveness, goblet cell hyperplasia, and lung fibrosis by modulating ROS and Nrf2.